“I Give It Everything for an Hour Then I Sleep for Four.” The Experience of Post-stroke Fatigue During Outpatient Rehabilitation Including the Perspectives of Carers: A Qualitative Study - Bicknell, Erin D.; Said, Catherine M.; Haines, Kimberley J.; Kuys, Suzanne (Frontiers in Neurology, 2022)
Background: Fatigue is a debilitating post-stroke symptom negatively impacting rehabilitation. Lack of acknowledgement from carers can be additionally distressing. The purpose of this study was to describe the experience of post-stroke fatigue during outpatient rehabilitation, including the perspectives of carers. Methods: This qualitative study was guided by descriptive phenomenology within a constructivist paradigm. Semi-structured interviews were conducted with stroke survivors experiencing fatigue (Fatigue Assessment Scale >23) and attending outpatient rehabilitation. Carers were also interviewed where identified, providing insight into their own and stroke survivor experiences. Data were analysed according to Colaizzi’s analytic method. Results: Fourteen stroke survivors (50% culturally and linguistically diverse), and nine carers participated. Six themes were identified: 1. The unpredictable and unprepared uncovering of fatigue; 2. Experience and adjustment are personal 3. Being responsible for self-managing fatigue; 4. Rehabilitation as a vehicle for improving fatigue; 5. Learning about fatigue is a self-directed problem-solving experience; 6. Family and carers can support or constrain managing fatigue. Conclusion: Despite engaging in outpatient rehabilitation, stroke survivors largely learnt to manage fatigue independent of healthcare professionals. Carers often facilitated learning, monitoring rehabilitation, daily routines, and fatigue exacerbation. Conversely, family could be dismissive of fatigue, and possess unrealistic expectations. Post-stroke fatigue must be considered by clinicians when delivering outpatient rehabilitation to stroke survivors. Clinicians should consistently screen for fatigue, provide flexible session scheduling, and educate about individual indicators and strategies for management. Clinicians should also explicitly engage carers who play a critical role in the management of fatigue.